PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA KARTU DOMINO TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMA - I Gusti Agung Ngurah Trisna Jayantika; Putu Suarniti Noviantari; I Putu Ade Andre Payadnya; I Gusti Ayu Virly Permatasari (Satya Widya, 2019)
This study aimed to determine whether the mathematical learning achievement of students who learned using cooperative learning mode of STAD assisted by domino card is better than the students who learned using conventional learning model. The type of this research was quasi-experimental research in which the post-test only controlled group design. The population of this research was students of 11th grade of SMA Negeri 6 Denpasar in academic year 2018/2019 totaling 321 students who were distrbuted into 9 classes. The sample was taken using Cluster Random Sampling technique where two classes were chosen as experimental class and control class. Data of students’ mathematical learning achievement were collected by test method. Data were analyzed using one-tail t-test with a significance level of 5%. The results of data analysis showed that the mathematics learning achievement of students who learned using cooperative learning model of STAD assisted by domino card was better than the mathematics learning achievement of students who learned using the conventional learning model in 11th grade of SMA Negeri 6 Denpasar in academic year 2018/2019.